ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI ALJABAR KELAS VII SMPN 1 JUWIRING - Nurul Wafa; Adi Ihsan Imami (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research aims to describe students errors in solving algebraic material problems. In addition, knowing what factors cause difficulties in completing algebraic material. The method used is descriptive qualitative. This research was conducted in one of the public junior high schools in Klaten Regency. The selection is based on the subject at the time of the researcher through preliminary observations with tests. So that the selected subjects were 5 students from a total of 34 students. These five form a strategy for collecting test data, unplanned interviews and student work records. Student errors in solving algebra material problems can be found in 4 errors seen from the results of research conducted including 1). incorrect knowledge of positive and negative operations 2) reading comprehension error-question 3) error in counting 4) Incorrect use of process.